Atopy patch test with house dust mite in Chinese patients with atopic dermatitis. (22nd June 2016) - Dou, X.; Kim, J.; Ni, C.Y.; Shao, Y.; Zhang, J.
Abstract: Background: The atopy patch test (APT) has been defined as an important tool in the diagnosis of cutaneous hypersensitivity caused by house dust mites in atopic dermatitis (AD). Objective: The aim of this study was to evaluate the diagnostic value of the APT to mite allergens by comparing its positive results with those of the skin prick test (SPT) and serum specific IgE test in Chinese AD patients. Methods: The APT, SPT and serum specific IgE test with Dermatophagoiodes pteronyssinus and Dermatophagoides farina were performed on a total of 120 patients with atopic dermatitis. Results: Overall, 37.5% of the patients showed a positive APT reaction to mite allergens. A statistically significant association was observed between positive APT results and air‐exposed eczema pattern. The positive APT results were not significantly associated with SCORAD scores and accompanied atopic respiratory disorders in AD patients. A higher frequency of APT positive reactions to mite allergens was observed in adolescent and adult patients. There was no significant difference in APT positivity between extrinsic patients (40.7%) and intrinsic patients (27.6%). Conclusion: This study identified house dust mite induced cutaneous hypersensitivity in Chinese patients with AD by APT, especially in air‐exposed distribution patterns or adolescent and adult patients. Both intrinsic and extrinsic AD patients showed positive APT reactions to house dust mite.